“Fishing for Stamps”: The Origins and Development of Unemployment Insurance for Canada’s Commercial Fisheries, 1941-71 - Lund, L. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1995)
AbstractUnemployment insurance (UI) benefits have had a huge impact on Canada's fishing communities since the St. Laurent government extended coverage to the industry in 1956. Nevertheless, the origins and development of this programme have not attracted much attention from historians. This paper seeks to rectify that situation and at the same time, shed some light on social policy formation at the federal level in post-war Canada. The weight of evidence indicates that influences external to the state were of great importance. A unique combination of circumstances in Newfoundland prompted that province's fishers to wage a grass roots campaign for insurance coverage, and their agitation, along with the efforts of their Cabinet representative, J.W. Pickersgill, eventually overcame significant opposition within the government. This extension of UI, despite being the subject of much criticism in recent years, was on balance, the best available short-term solution to the Newfoundland fisheries problem: the St. Laurent government's real policy failure was its conservative approach to long-term fisheries development.